Efektivitas Kemitraan Usaha Ternak Sapi Potong terhadap Pendapatan Petani-Peternak di Kabupaten Timor Tengah Utara Provinsi Nusa Tenggara Timur - Putra Suardika; IGAA. Ambarawati; I Made Sudarma (JURNAL MANAJEMEN AGRIBISNIS, 2015)
The Ministry of Agriculture targeted the farmers' per capita income of IDR 7.93 million/year in 2014. This target has not been achieved because farm productivity still low. A beef cattle business was developed by Yayasan Mitra Tani Mandiri (YMTM) through a partnership with livestock farmers, however it hasn’t been known effectiveness level of the partnership. The study was to determine the effectiveness level of beef cattle business partnerships; the influence of the characteristics of livestock farmers, the mentoring from YMTM and the seven techniques of beef cattle business on the effectiveness of the partnership; and the influence of the effectiveness of the partnerships on the livestock farmers’ income. Population of the study were farmers who received cattle from YMTM. Sampling was conducted through proportional stratified, covering 156 livestock farmers. The data were analyzed by method quantitative descriptive and relationship analysis with SmartPLS. The beef cattle business partnership between YMTM and the livestock farmers in TTU can be classified into the sufficient category of effective. All the exogenous factors, namely the characteristics of livestock farmers, mentoring YMTM and the seven techniques of beef cattle business have a significant effect on the effectiveness of the partnership. The average of the weight gain of cattle is 262 gram/catlle/day, which is tended in 2.1 years period. Likewise, the income of livestock farmers is influenced significantly by the effectiveness of the partnership. Revenue from the beef cattle business partnerships contribute on average 29.91 % (IDR 3,574,002) to the livestock farmers’ total income (IDR 11,949,342). Suggestions which can be made to improve the partnership including increasing the weight gain of cattle per day, select calves from good stock lines, increasing the frequency of trainings which deal with the techniques and management of the  cattle business, processing livestock manure, and processing the remains of crops into nutritious fodder.